The Effectiveness of Different Doses or Types of Vitamin D Supplementation in HIV-Positive Individuals in Lahore: Effectiveness of Vitamin D Supplementation in HIV-Positive Individuals - Majeed, Fatima; Saleem, Javeria; Ullah, Kifayat; Rafique, Shamsa; Mehar Javaid Bukhari, Gul; Dilnawaz, Aimen; Tariq, Ali; Shahbaz, Ferheen (Pakistan Journal of Health Sciences, 2023)
The average lifespan of people suffering from HIV-AIDS is estimated to be 9 to 11 years, with Vitamin D deficiency as one of the most common phenomena among them. Anti-Retroviral Therapy (ART) could significantly enhance the quality of life of HIV-AIDS patients; however, it further decreases Vitamin D serum levels among them. Objectives: To evaluate the impact of vitamin D supplementation on immune function, viral load, and other health outcomes in HIV-positive individuals. Methods: This was a descriptive study conducted on a sample of 95 HIV-diagnosed patients aged 19 to 50 years in Punjab, Pakistan. Patients were selected from an AIDS control clinic and prescribed antiretroviral therapy. Baseline assessments were conducted using a structured evaluation questionnaire, and biochemical results were used to classify vitamin D deficiency. Results: The study presents information on PCR viral load counts in HIV patients, including minimum (50), and maximum (750,000) values, mean (32,475) with standard deviation (155,343), 5% sheared mean (28), and the 95% confidence interval (17,802 to 47,148) for the average. Results showed that HIV-positive patients taking vitamin D supplementation had a lower mean rank (50.07) compared to those not taking supplements (57.00), with a difference of 275.5 in the sum of ranks between the two groups. Inferential statistics suggested that vitamin D plays a significant role in improving the prognosis of HIV patients taking ART, with a significance value of 0.0032. Conclusion: The present study concludes that Vitamin D supplementation has a significant role in improving the life status of HIV patients.